PENGARUH KARAKTERISTIK KOMITE AUDIT TERHADAP PENGUNGKAPAN ETIKA (Studi Empiris pada Perusahaan Non-Keuangan yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2014) - Bayu Wisnu Pradana; Dwi Ratmono (Diponegoro Journal of Accounting, 2016)
This study aims to examine the effect of the proportion of independent members of the audit committee, the number of audit committee meetings, the size of the audit committee, the average tenure of audit committee members, and members of the audit committee with multiple-Directorship on ethics disclosure.This study uses data time series in 2012, 2013 and 2014 annual reports of companies listed on the Stock Exchange. Purposive sampling chosen as the sampling method. The number of samples in this research are 248 companies. This study uses regression analysis.The results showed that only the number of audit committee meetings are significant positive effect on the ethics disclosure. While the proportion of independent members of the audit committee, the audit committee size, the average tenure of members of the audit committee and member of the audit committee with multiple-Directorship does not significantly influence the ethics disclosure.